((The impact of special exercises in the development of the transitional speed of the youth of Al-Khalis football club) (Journal of the College of Basic Education, 2026)
Football is one of the team games that requires its players to possess special physical and skill abilities and to perform with high efficiency throughout the game, and the construction of training curricula with the style is not based on modern foundations that lack the link with the modern style that keeps pace with the developments in the modern game of football, the researcher focused on getting out of the traditional pattern of the training curriculum and making changes in the development of skill and physical abilities, and used the experimental method by designing two experimental and control groups with tribal and dimensional testing, and the research community was chosen in a deliberate way, and the researcher chose a his research, which included the players of Diyala clubs The research community reached (124) players and one group of players was selected randomly and they represent the experimental group of the pure club and their number is( 12) players from the second control group who represent (14 )players from the Hebah club for juniors where the research community is represented in the province of (7) are (Al-Khalis club, Al-Shahid Arkan club, shahrban club Baquba club, jadida Al-Shatt club, Habhab club, Diyala club,) as the research community reached (12) players and one group of players was selected randomly and they represent the experimental group of the pure club and their number is (12) players from the researcher developed and implemented special exercises for the experimental group of the research sample at the stage of special preparation, where The training curriculum included( 24) units divided into (3) days a week and in fact two units of each week on the days allocated to the club, and the researcher concluded that the special exercises by the researcher had a role in the effective development of the transition speed of the pure club, and these exercises have an effective role in developing the physical abilities of the research sample.